IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PROGRAM KEMUHAMMADIYAHAN/KEAISYIYAHAN DI TK AISYIYAH BUSTANUL ATHFAL Vl MANGGALA KOTA MAKASSAR - Nur Alim Amri; Reni Putri Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to find out how the implementation of the project to strengthen the Pancasila student profile through the Muhammadiyah/Keaisyiyahan program at TK Aisyiyah Bustanul Athfal VI Manggala, Makassar City. This research was carried out at Aisyiyah Bustanul Athfal V1 Manggala Kindergarten, Makassar City. The informants in this study were school principals and teachers in group B1 Aisyiyah Kindergarten Bustanul Athfal V1 Manggala Makassar City. The method of data collection in this study is qualitative data collection, namely observation, interviews, and documentation as well as data analysis techniques are descriptive qualitative. The results showed that the implementation of the project to strengthen the profile of Pancasila students through the Kemuhammadiyahan/keaisyiyahan program at TK Aisyiyah Bustanul Athfal VI Manggala Makassar City is in accordance with the dimensions of the Pancasila student profile, one of which is faith, piety to the One and Only God and has noble character which is carried out with habit. perform dhuha prayers, recite the Koran, and pray every day before starting learning or after the end of learning. So, after the implementation of the project to strengthen the profile of Pancasila students in Muhammadiyah/Aisyiyah activities, the implementation is still the same as before the project was implemented to strengthen the profile of Pancasila students.